Positively charged acid and alkali resistant composite nanofiltration membrane as well as preparation method and application thereof

By grafting quaternary ammonium and quaternary phosphorus salt groups in the nanofiltration membrane separation layer and adopting a specific polymer structure, the existing nanofiltration membrane has poor tolerance and low magnesium lithium separation efficiency in acid and alkali environments, achieving efficient magnesium lithium separation and good acid and alkali resistance.

CN119565395AActive Publication Date: 2025-03-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311141335.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-05
Publication Date
2025-03-07
Estimated Expiration
2043-09-05

AI Technical Summary

Technical Problem

The existing nanofiltration membranes have poor tolerance in acid-base environments and low magnesium-lithium separation efficiency.

Method used

A positively charged and alkali-resistant composite nanofiltration membrane is used, and its separation layer is grafted with quaternary ammonium salt groups and/or quaternary phosphorus salt groups through N atoms to enhance the positive electrical properties of the membrane surface and improve chemical inertia and hydrogen bond density through specific polymer structures.

Benefits of technology

The acid and alkali resistance of the nanofiltration membrane and the separation efficiency of magnesium and lithium magnesium are improved, while maintaining high water flux.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565395A_ABST
    Figure CN119565395A_ABST
Patent Text Reader

Abstract

The invention relates to the field of membranes, and discloses a positively charged acid and alkali resistant composite nanofiltration membrane as well as a preparation method and application thereof. The positively charged acid and alkali resistant composite nanofiltration membrane sequentially comprises a bottom layer, a porous middle layer and an acid and alkali resistant separation layer, the acid and alkali resistant separation layer is grafted with a quaternary ammonium salt group as shown in a formula I and / or a quaternary phosphonium salt group as shown in a formula II through N atoms; # imgabs0 # is shown as a formula I; # imgabs 1 # is shown as a formula II; wherein R1 is a substituted or unsubstituted alkylene group of C1 to C9; r < 2 >, R < 3 > and R < 4 > are independently selected from C1-C3 alkyl groups or phenyl groups; r5 is an alkylene group of C1-C6, a phenyl group or an aralkyl group of C7-C10; r < 6 >, R < 7 > and R < 8 > are respectively and independently phenyl or C7-C10 aralkyl; x is halogen. Therefore, the nanofiltration membrane has a high magnesium-lithium separation coefficient while keeping high water flux.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the membrane field, and in particular to a positively charged acid- and alkali-resistant composite nanofiltration membrane and a preparation method and application thereof. Background Art

[0002] Nanofiltration is a membrane separation process driven by pressure. Nanofiltration membrane is between ultrafiltration membrane and reverse osmosis membrane, with a pore size of 1-2nm and a molecular weight cutoff of 200-2000Da. Due to its advantages such as high separation efficiency, low energy consumption and small footprint, nanofiltration separation is widely used in many fields such as wastewater treatment, seawater desalination, chemical separation, food and drug processing, etc., and occupies an important position in modern separation and purification.

[0003] The mechanism of nanofiltration separation is relatively complex. It is generally believed that the nanofiltration separation performance is the result of the combined effect of size screening effect and Donnan effect. In addition to the density of the membrane itself, there is significant charge selectivity in the nanofiltration separation process. Polyamide film composite nanofiltration membrane is the most widely used commercial nanofiltration membrane. The acyl chloride groups on the membrane surface are hydrolyzed to form a large number of carboxyl groups, making the membrane surface negatively charged. Due to the influence of the Donnan effect, the membrane has a low removal rate for high-valent cations, which limits its application in some special fields. The more representative ones include the extraction of Mg from salt lake brine for lithium. 2+ and Li + Separation of positively charged ions, softening of drinking water, treatment of heavy metal wastewater, refining of crude salt, and concentration and separation of special substances in the food industry. In addition, in the process of intercepting positively charged ions and dye molecules, positively charged nanofiltration membranes have better anti-pollution performance. Based on the above, high-performance positively charged nanofiltration membranes have good application prospects.

[0004] In addition to the charged properties of the membrane, some application scenarios also have higher requirements for the membrane's acid resistance. In the hydrometallurgical process, an acidic leachate containing metal cations such as lithium, nickel, cobalt, and manganese is obtained. The positively charged nanofiltration membrane can effectively separate monovalent and high-valent cations, and then reverse osmosis technology is used to concentrate and enrich them respectively, thereby realizing the comprehensive utilization of resources. In the adsorption-membrane combined lithium extraction process, the desorption process of the adsorbent needs to be carried out under acidic conditions, which makes the original solution of the nanofiltration process acidic. However, under acidic conditions, the C=O bond in the polyamide structure is easily affected by H + The nucleophilic electrons attack the amide bonds, causing hydrolysis of the amide bonds, which destroys the structure of the membrane separation layer and reduces the retention performance.

[0005] Therefore, there is an urgent need to develop a positively charged nanofiltration membrane with a simple preparation method and excellent acid resistance to overcome the limitations of existing nanofiltration membranes in the above application scenarios. Summary of the invention

[0006] The purpose of the present invention is to overcome the problems of poor acid and alkali tolerance and low magnesium-lithium separation efficiency of existing nanofiltration membranes, and to provide a positively charged acid and alkali resistant composite nanofiltration membrane and its preparation method and application. The specific polymer structure of the separation layer in the positively charged acid and alkali resistant composite nanofiltration membrane has good chemical inertness and a high hydrogen bond density, so that the separation layer has high acid and alkali resistance; and the grafting of specific quaternary ammonium salt groups and / or quaternary phosphonium salt groups can enhance the positive charge of the membrane surface, so that the nanofiltration membrane has a high magnesium-lithium separation coefficient while maintaining a high water flux.

[0007] In order to achieve the above-mentioned object, the first aspect of the present invention provides a positively charged acid- and alkali-resistant composite nanofiltration membrane, wherein the positively charged acid- and alkali-resistant composite nanofiltration membrane comprises a bottom layer, a porous middle layer and an acid- and alkali-resistant separation layer in sequence;

[0008] Wherein, the acid-base resistant separation layer is grafted with the quaternary ammonium salt group shown in formula I and / or the quaternary phosphonium salt group shown in formula II by N atom;

[0009]

[0010] Among them, R 1 is a C1-C9 substituted or unsubstituted alkylene group; R 2 , R 3 , R 4 R is independently selected from C1-C3 alkyl or phenyl; 5 is a C1-C6 alkylene group, a phenyl group or a C7-C10 aralkyl group; R 6 , R 7 , R 8 Each is independently phenyl or C7-C10 aralkyl;

[0011] X is halogen.

[0012] The second aspect of the present invention provides a method for preparing a positively charged acid- and alkali-resistant composite nanofiltration membrane, wherein the preparation method comprises the following steps:

[0013] S1. Under stirring, adding a first solution containing a quaternary ammonium halogenate salt and / or a quaternary phosphonium halogenate salt and a catalyst to a second solution containing a polyamine to react and obtain a modified polyamine;

[0014] S2, preparing a porous supporting layer on the bottom layer;

[0015] S3, after the surface of the porous support layer is first contacted with the aqueous phase containing the modified polyamine in step S1, and then secondly contacted with the organic phase containing the polyvalent polar monomer, heat-treated to obtain the positively charged acid-base resistant composite nanofiltration membrane;

[0016] The halogenated quaternary ammonium salt has a structure shown in formula III; the halogenated quaternary phosphonium salt has a structure shown in formula IV;

[0017]

[0018] Among them, R 1 ' is a C1-C9 substituted or unsubstituted alkylene group; R 2 '、R 3 '、R 4 ' are each independently selected from C1-C3 alkyl or phenyl; R 5 ' is a C1-C6 alkylene group, a phenyl group or a C7-C10 aralkyl group; R 6 '、R 7’ , R 8 'Each independently is phenyl or C7-C10 aralkyl;

[0019] X and X 1 are each independently halogen.

[0020] The third aspect of the present invention provides a positively charged acid- and alkali-resistant composite nanofiltration membrane prepared by the above-mentioned preparation method.

[0021] A fourth aspect of the present invention provides an application of the above-mentioned positively charged acid- and alkali-resistant composite nanofiltration membrane in the field of water treatment and separation.

[0022] Through the above technical scheme, the positively charged acid-base resistant composite nanofiltration membrane provided by the present invention and its preparation method and application can achieve the following beneficial effects:

[0023] The specific polymer structure in the separation layer of the positively charged acid- and alkali-resistant composite nanofiltration membrane provided by the present invention gives the separation layer good chemical inertness and high hydrogen bond density, so that the separation layer has good acid and alkali resistance; the acid and alkali-resistant separation layer is grafted with specific quaternary ammonium salt groups and / or quaternary phosphonium salt groups by N atoms, so that the positive charge density of the nanofiltration membrane is significantly improved, and the repulsive effect between the positive charges is used to improve the nanofiltration membrane's resistance to Mg 2+ The retention effect can be improved, thereby improving the magnesium-lithium separation efficiency of the nanofiltration membrane while maintaining a high water flux of the nanofiltration membrane.

[0024] The preparation method of the positively charged acid- and alkali-resistant composite nanofiltration membrane provided by the present invention comprises the following steps: subjecting a quaternary ammonium halogenated salt and / or a quaternary phosphonium halogenated salt to a biochemical reaction with a polyamine under the action of an alkaline catalyst, modifying the polyamine, and polymerizing the modified polyamine with a polar monomer to introduce a group with a strong conjugated effect and good chemical inertness, thereby greatly improving the acid- and alkali-resistant property of the nanofiltration membrane; at the same time, the positive charge density on the surface of the separation membrane is high, thereby improving the nanofiltration membrane's resistance to Mg. 2+ The interception effect can improve the magnesium-lithium separation efficiency of the nanofiltration membrane, while maintaining a high water flux of the nanofiltration membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the infrared spectrum of the positively charged acid- and alkali-resistant composite nanofiltration membrane prepared in Example 1. DETAILED DESCRIPTION

[0026] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0027] The first aspect of the present invention provides a positively charged acid- and alkali-resistant composite nanofiltration membrane, wherein the positively charged acid- and alkali-resistant composite nanofiltration membrane comprises a bottom layer, a porous middle layer and an acid- and alkali-resistant separation layer in sequence;

[0028] Wherein, the acid-base resistant separation layer is grafted with the quaternary ammonium salt group shown in formula I and / or the quaternary phosphonium salt group shown in formula II by N atom;

[0029]

[0030] Among them, R 1 is a C1-C9 substituted or unsubstituted alkylene group; R 2 , R 3 , R 4 R is independently selected from C1-C3 alkyl or phenyl; 5 is a C1-C6 alkylene group, a phenyl group or a C7-C10 aralkyl group; R 6 , R 7 , R 8 Each is independently phenyl or C7-C10 aralkyl;

[0031] X is halogen.

[0032] In the present invention, * refers to the quaternary ammonium salt group or quaternary phosphonium salt group and the -NH-, The location where the connection is made into a bond.

[0033] In the present invention, specific quaternary ammonium salt groups and / or quaternary phosphonium salt groups are grafted into the acid-base resistant separation layer, so that the positively charged acid-base resistant composite nanofiltration membrane has a high magnesium-lithium separation coefficient while maintaining a high water flux, and is particularly suitable for the field of water treatment separation.

[0034] In the present invention, R 1 It may be a branched chain alkylene group or a linear chain alkylene group.

[0035] Furthermore, R 1is a C1-C6 substituted or unsubstituted alkylene group, R 2 , R 3 , R 4 Each independently is CH 3 ; R 5 is a C1-C3 alkylene group, a phenyl group or a C8-C10 aralkyl group; R 6 , R 7 , R 8 Each is independently phenyl.

[0036] Furthermore, R 1 It is a C1-C3 unsubstituted alkylene group, wherein the substituent is a hydroxyl group or a carboxyl group, preferably a hydroxyl group.

[0037] Furthermore, X is Cl, Br or I.

[0038] Furthermore, the acid-base resistant separation layer is selected from at least one of a polyurea separation layer, a polytriazineamine separation layer, a polysulfonamide separation layer, a poly(triazineamine-urea) separation layer, a poly(sulfonamide-urea) separation layer, a poly(triazineamine-sulfonamide) separation layer and a poly(triazineamine-sulfonamide-urea) separation layer, preferably at least one of a polyurea separation layer, a polytriazineamine separation layer and a polysulfonamide separation layer.

[0039] In one embodiment of the present invention, in Formula I, R 1 For ethylene, Propylene, butylene, pentylene or hexylene; R 2 , R 3 , R 4 is methyl, ethyl or phenyl; X is Cl, Br or I.

[0040] In one embodiment of the present invention, Formula II, R 5 is propylene, ethylene, methylene or R 6 , R 7 , R 8 is phenyl; X is Cl, Br or I.

[0041] According to the present invention, the content of nitrogen atoms in the quaternary ammonium salt groups in the positively charged acid- and alkali-resistant composite nanofiltration membrane is 10-20 at.%.

[0042] In the present invention, when the content of nitrogen atoms in the quaternary ammonium salt groups in the positively charged acid- and alkali-resistant composite nanofiltration membrane meets the above-mentioned range, the positively charged acid- and alkali-resistant composite nanofiltration membrane has a high surface electrode potential and a small average pore size, so that the positively charged acid- and alkali-resistant composite nanofiltration membrane has a high magnesium-lithium separation coefficient; at the same time, the acid- and alkali-resistant separation layer will not excessively affect the water flux of the membrane through the quaternary ammonium salt groups shown in I grafted by N atoms, so that the membrane maintains a good water flux.

[0043] Furthermore, the content of nitrogen atoms in the quaternary ammonium salt groups in the positively charged acid- and alkali-resistant composite nanofiltration membrane is 10-15 at.%.

[0044] According to the present invention, the content of phosphorus atoms in the positively charged acid- and alkali-resistant composite nanofiltration membrane is 0.4-3 at.%.

[0045] In the present invention, when the content of phosphorus atoms in the positively charged acid- and alkali-resistant composite nanofiltration membrane meets the above-mentioned range, the positively charged acid- and alkali-resistant composite nanofiltration membrane has a high surface electrode potential and a small average pore size, so that the positively charged acid- and alkali-resistant composite nanofiltration membrane has a high magnesium-lithium separation coefficient; at the same time, the acid- and alkali-resistant separation layer will not excessively affect the water flux of the membrane through the quaternary phosphonium salt group shown in N atom formula II, so that the membrane maintains good separation efficiency.

[0046] Furthermore, the content of phosphorus atoms in the positively charged acid- and alkali-resistant composite nanofiltration membrane is 0.5-2 at.%.

[0047] According to the present invention, the surface Zeta potential of the positively charged acid- and alkali-resistant composite nanofiltration membrane is 0-30 mV.

[0048] In the present invention, when the surface Zeta potential of the positively charged acid- and alkali-resistant composite nanofiltration membrane meets the above range, it indicates that the composite nanofiltration membrane has a high surface electrode potential, and when it is used for lithium-magnesium separation in an acid- and alkali-resistant environment, it can better exclude Mg. 2+ , so that the Mg in the liquid 2+ It is not easy to pass through the separation membrane, and at the same time, it can make Li + As much as possible, the membrane can achieve a higher magnesium-lithium separation efficiency.

[0049] In the present invention, the surface Zeta potential of the positively charged acid- and alkali-resistant composite nanofiltration membrane refers to the surface Zeta potential at pH=7.

[0050] Furthermore, the surface Zeta potential of the positively charged acid- and alkali-resistant composite nanofiltration membrane is 5-25 mV.

[0051] According to the present invention, the average pore size of the positively charged acid- and alkali-resistant composite nanofiltration membrane is 0.1-0.4 nm.

[0052] In the present invention, when the average pore size of the positively charged acid- and alkali-resistant composite nanofiltration membrane meets the above range, it indicates that the positively charged acid- and alkali-resistant composite nanofiltration membrane has a high density, and when it is used for lithium-magnesium separation in an acid- and alkali-resistant environment, it can better exclude Mg. 2+ , so that the Mg in the liquid 2+ It is not easy to pass through the separation membrane, and at the same time, it can make Li + As much as possible, so as to obtain a higher magnesium-lithium separation efficiency.

[0053] Furthermore, the average pore size of the positively charged acid- and alkali-resistant composite nanofiltration membrane is 0.2-0.3 nm.

[0054] According to the present invention, the contact angle of the positively charged acid- and alkali-resistant composite nanofiltration membrane is 30-80°.

[0055] In the present invention, the positively charged acid- and alkali-resistant composite nanofiltration membrane has a contact angle within the range of the present invention, which indicates that the positively charged acid- and alkali-resistant composite nanofiltration membrane has good hydrophilicity and can enable the composite nanofiltration membrane to have a high water flux.

[0056] Furthermore, the contact angle of the positively charged acid- and alkali-resistant composite nanofiltration membrane is 30-60°.

[0057] In the present invention, the bottom layer and the porous support layer are not specifically limited, and can be made of various existing materials that have a certain strength and can be used for nanofiltration and reverse osmosis membranes.

[0058] In the present invention, the bottom layer is a non-woven fabric, preferably polyester and / or polyethylene.

[0059] In the present invention, the porous support layer material is at least one selected from polyethersulfone, polysulfone, polyarylether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride and polyaryletherketone.

[0060] In the present invention, the acid-base resistant separation layer is selected from at least one of a polyurea separation layer, a polytriazineamine separation layer, a polysulfonamide separation layer, a poly(triazineamine-urea) separation layer, a poly(sulfonamide-urea) separation layer, a poly(triazineamine-sulfonamide) separation layer and a poly(triazineamine-sulfonamide-urea) separation layer, preferably at least one of a polyurea separation layer, a polytriazineamine separation layer and a polysulfonamide separation layer.

[0061] Furthermore, the acid-base resistant separation layer is generated by interfacial polymerization of polyamines modified by quaternary ammonium halides and / or quaternary phosphonium halides and polypolar monomers.

[0062] According to the present invention, the polyvalent polar monomer is selected from at least one of polyvalent isocyanates, triazine compounds containing at least two C-Cl bonds, and polyvalent sulfonyl chlorides.

[0063] In the present invention, polyamine reacts with at least one of polyisocyanate, triazine compound containing at least two C-Cl bonds and polysulfonyl chloride to introduce groups with strong conjugation effect and good chemical inertness into the nanofiltration membrane. The generated polymer has good structural stability in both acidic and alkaline environments, so that the acid and alkali resistance of the nanofiltration membrane is greatly improved, and it is particularly suitable for acidic environments.

[0064] According to the present invention, the polyamine is at least one of polyethyleneimine, polyethyleneamine, triethylenetetramine, tetraethylenepentamine, diethylenetriamine, polyethylenepolyamine, piperazine, m-phenylenediamine and p-phenylenediamine; preferably polyethyleneimine and / or polyethylenepolyamine.

[0065] According to the present invention, the polyisocyanate is selected from at least one of meta-phenylenediisocyanate, isophorone diisocyanate, 1,6-hexamethylene diisocyanate, toluene-2,6-diisocyanate, 1,4-phenylenediisocyanate, toluene-2,4-diisocyanate, 4,4'-methylenebis(phenyl isocyanate), 1,3-phenylenediisocyanate, 3,3'-dichloro-4,4'-diisocyanatebiphenyl, dicyclohexylmethane-4,4'-diisocyanate, trimethylhexamethylene diisocyanate, L-lysine-ethyl ester-diisocyanate, 1,4-cyclohexyl diisocyanate and 4-chloro-6-methyl-meta-phenylenediisocyanate; preferably 1,4-phenylenediisocyanate and / or 1,3-phenylenediisocyanate.

[0066] According to the present invention, the triazine compound containing at least two C-Cl bonds is selected from at least one of cyanuric chloride, 2,4-dichloro-1,3,5-triazine, 2,5-dichloro-1,3,5-triazine and 2,4-dichloro-6-phenyl-1,3,5-triazine; preferably cyanuric chloride.

[0067] According to the present invention, the polysulfonyl chloride is selected from at least one of 1,3-benzenedisulfonyl chloride, 1,2-benzenedisulfonyl chloride, 1,4-benzenedisulfonyl chloride, 2,4-disulfonyl chloride-mesitylene, biphenyl-4,4'-disulfonyl chloride, 4,5-dichloro-1,3-benzenedisulfonyl chloride, 2,6-naphthalene disulfonyl chloride, 1,3-naphthalene disulfonyl chloride, 2,7-naphthalene disulfonyl chloride, 1,3,5-benzene trisulfonyl chloride and 1,3,6-naphthalene trisulfonyl chloride; preferably 1,3-benzenedisulfonyl chloride.

[0068] In the present invention, the halogenated quaternary ammonium salt has a structure shown in Formula III;

[0069]

[0070] Among them, R 1 ' is a C1-C9 substituted or unsubstituted alkylene group; R 2 '、R 3 '、R 4 ' are each independently selected from C1-C3 alkyl or phenyl; X 1 and X are each independently halogen.

[0071] Furthermore, R 1 ' is a C1-C6 substituted or unsubstituted alkylene or phenyl; R 2 '、R 3'、R 4 'Each independently is CH 3 ; X is Cl, Br or I; X 1 is F, Cl, Br or I.

[0072] In a specific embodiment of the present invention, R1' is a C1-C3 unsubstituted alkylene group, wherein the substituent is a hydroxyl group or a carboxyl group, preferably a hydroxyl group.

[0073] In a specific embodiment of the present invention, the halogenated quaternary ammonium salt is selected from at least one of 2-chloroethyltrimethylammonium chloride, 2-chloroethyltriethylammonium chloride, 2-chloroethyltriphenylammonium chloride, 3-chloro-2-hydroxypropyltrimethylammonium chloride, 3-chloropropyltrimethylammonium chloride, 4-chlorobutyltrimethylammonium chloride, 5-chloropentyltrimethylammonium chloride, 6-chlorohexyltrimethylammonium chloride, 2-bromoethyltrimethylammonium bromide, 3-bromopropyltrimethylammonium bromide, 4-bromobutyltrimethylammonium bromide, 5-bromopentyltrimethylammonium bromide, 6-bromohexyltrimethylammonium bromide, iodomethyltrimethylammonium iodide, 2-iodoethyltrimethylammonium iodide, 3-iodopropyltrimethylammonium iodide, 4-iodobutyltrimethylammonium iodide, 5-iodopentyltrimethylammonium iodide and 6-iodohexyltrimethylammonium iodide.

[0074] In the present invention, the halogenated quaternary phosphonium salt has a structure shown in Formula IV;

[0075]

[0076] Among them, R 5 ' is a C1-C6 alkylene group, a phenyl group or a C7-C10 aralkyl group; R 6 '、R 7 '、R 8 'Each independently is phenyl or C7-C10 aralkyl;

[0077] X and X 1 are each independently halogen.

[0078] Furthermore, R 5 ' is phenyl or C8-C10 aralkyl; R 6 '、R 7 '、R 8 ' are each independently phenyl; R 1 ' is a C1-C3 unsubstituted alkylene group, wherein the substituent is a hydroxyl group or a carboxyl group.

[0079] Furthermore, X is Cl, Br or I.

[0080] Furthermore, X 1 is F, Cl, Br or I.

[0081] In a specific embodiment of the present invention, the halogenated quaternary phosphonium salt is selected from 3-bromopropyl triphenyl phosphonium bromide, 2-bromoethyl triphenyl phosphonium bromide, 1-bromoethyl triphenyl phosphonium bromide, bromomethyl triphenyl phosphonium bromide, 3-chloropropyl triphenyl phosphonium chloride, 2-chloroethyl triphenyl phosphonium chloride, 1-chloroethyl triphenyl phosphonium chloride, chloromethyl triphenyl phosphonium chloride, 3-iodopropyl triphenyl phosphonium iodide, 2-iodoethyl triphenyl phosphonium iodide, 1-iodoethyl triphenyl phosphonium iodide, iodomethyl triphenyl phosphonium bromide, 4 At least one of -bromomethylbenzyltriphenylphosphonium bromide, 2-bromomethylbenzyltriphenylphosphonium bromide, 3-bromomethylbenzyltriphenylphosphonium bromide, 4-chloromethylbenzyltriphenylphosphonium chloride, 2-chloromethylbenzyltriphenylphosphonium chloride, 3-chloromethylbenzyltriphenylphosphonium chloride, 4-iodomethylbenzyltriphenylphosphonium iodide, 2-iodomethylbenzyltriphenylphosphonium iodide and 3-iodomethylbenzyltriphenylphosphonium iodide, preferably 3-bromopropyltriphenylphosphonium bromide and / or 4-bromomethylbenzyltriphenylphosphonium bromide.

[0082] According to the present invention, the present invention does not particularly limit the thickness of the bottom layer, the porous support layer, and the acid-base resistant separation layer, which can be a conventional choice in the field, but in order to enable the three layers to play a better synergistic role, so that the obtained positively charged acid-base resistant composite nanofiltration membrane can better have an excellent magnesium-lithium separation coefficient and a higher water flux, preferably, the thickness of the bottom layer is 30-150μm, preferably 50-120μm; the thickness of the porous support layer is 10-100μm, preferably 30-60μm; the thickness of the acid-base resistant separation layer is 10-500nm, preferably 50-300nm.

[0083] The second aspect of the present invention provides a method for preparing a positively charged acid- and alkali-resistant composite nanofiltration membrane, wherein the preparation method comprises the following steps:

[0084] S1. Under stirring, adding a first solution containing a quaternary ammonium halogenate salt and / or a quaternary phosphonium halogenate salt and a catalyst to a second solution of a polyamine to react and obtain a modified polyamine;

[0085] S2, preparing a porous supporting layer on the bottom layer;

[0086] S3, after the surface of the porous support layer is first contacted with the aqueous phase containing the modified polyamine in step S1, and then secondly contacted with the organic phase containing the polyvalent polar monomer, heat-treated to obtain the positively charged acid-base resistant composite nanofiltration membrane;

[0087] The halogenated quaternary ammonium salt has a structure shown in formula III; the halogenated quaternary phosphonium salt has a structure shown in formula IV;

[0088]

[0089] Among them, R1 ' is a C1-C9 substituted or unsubstituted alkylene group; R 2 '、R 3 '、R 4 ' are each independently selected from C1-C3 alkyl or phenyl; R 5 ' is a C1-C6 alkylene group, a phenyl group or a C7-C10 aralkyl group; R 6 '、R 7 '、R 8 'Each independently is phenyl or C7-C10 aralkyl;

[0090] X and X 1 are each independently halogen.

[0091] In the present invention, in the presence of an alkaline catalyst, a polyamine is grafted with a specific quaternary ammonium salt group and / or a quaternary phosphonium salt group to obtain a positively charged modified polyamine; after the polyamine and the polar monomer are interfacially polymerized, a group with good chemical inertness is introduced, thereby improving the positive charge density and acid-base tolerance of the nanofiltration membrane surface, so that the nanofiltration membrane has a high magnesium-lithium separation coefficient while maintaining a high water flux, and can still maintain a high water flux and have a relatively good magnesium-lithium separation performance in an acid-base environment.

[0092] Furthermore, R 1 ' is a C1-C6 substituted or unsubstituted alkylene group; R 2 '、R 3 '、R 4 'Each independently is CH 3 ; R 5 ' is phenyl or C8-C10 aralkyl; R 6 '、R 7 '、R 8 ' are each independently phenyl.

[0093] Furthermore, R 1 ' is a C1-C3 unsubstituted alkylene group, wherein the substituent is a hydroxyl group or a carboxyl group, preferably a hydroxyl group.

[0094] Furthermore, X is Cl, Br or I.

[0095] Furthermore, X 1 is F, Cl, Br or I.

[0096] According to the present invention, the halogenated quaternary ammonium salt is selected from at least one of 2-chloroethyltrimethylammonium chloride, 2-chloroethyltriethylammonium chloride, 2-chloroethyltriphenylammonium chloride, 3-chloro-2-hydroxypropyltrimethylammonium chloride, 3-chloropropyltrimethylammonium chloride, 4-chlorobutyltrimethylammonium chloride, 5-chloropentyltrimethylammonium chloride, 6-chlorohexyltrimethylammonium chloride, 2-bromoethyltrimethylammonium bromide, 3-bromopropyltrimethylammonium bromide, 4-bromobutyltrimethylammonium bromide, 5-bromopentyltrimethylammonium bromide, 6-bromohexyltrimethylammonium bromide, iodomethyltrimethylammonium iodide, 2-iodoethyltrimethylammonium iodide, 3-iodopropyltrimethylammonium iodide, 4-iodobutyltrimethylammonium iodide, 5-iodopentyltrimethylammonium iodide and 6-iodohexyltrimethylammonium iodide; preferably 2-chloroethyltrimethylammonium chloride and / or 3-bromopropyltrimethylammonium bromide.

[0097] According to the present invention, the halogenated quaternary phosphonium salt is selected from 3-bromopropyl triphenyl phosphonium bromide, 2-bromoethyl triphenyl phosphonium bromide, 1-bromoethyl triphenyl phosphonium bromide, bromomethyl triphenyl phosphonium bromide, 3-chloropropyl triphenyl phosphonium chloride, 2-chloroethyl triphenyl phosphonium chloride, 1-chloroethyl triphenyl phosphonium chloride, chloromethyl triphenyl phosphonium chloride, 3-iodopropyl triphenyl phosphonium iodide, 2-iodoethyl triphenyl phosphonium iodide, 1-iodoethyl triphenyl phosphonium iodide, iodomethyl triphenyl phosphonium bromide, 4-bromomethyl At least one of benzyltriphenylphosphonium bromide, 2-bromomethylbenzyltriphenylphosphonium bromide, 3-bromomethylbenzyltriphenylphosphonium bromide, 4-chloromethylbenzyltriphenylphosphonium chloride, 2-chloromethylbenzyltriphenylphosphonium chloride, 3-chloromethylbenzyltriphenylphosphonium chloride, 4-iodomethylbenzyltriphenylphosphonium iodide, 2-iodomethylbenzyltriphenylphosphonium iodide and 3-iodomethylbenzyltriphenylphosphonium iodide; preferably 3-bromopropyltriphenylphosphonium bromide and / or 4-bromomethylbenzyltriphenylphosphonium bromide.

[0098] According to the present invention, the concentration of the halogenated quaternary ammonium salt and / or the halogenated quaternary phosphonium salt in the first solution is 0.5 wt %-20 wt %.

[0099] In the present invention, when the concentration of the halogenated quaternary ammonium salt and / or the halogenated quaternary phosphonium salt in the first solution in step S1 is controlled to meet the above range, the prepared positively charged acid- and alkali-resistant composite nanofiltration membrane has a high magnesium-lithium separation coefficient; at the same time, the quaternary ammonium salt groups and / or quaternary phosphonium salt groups grafted on the surface of the acid- and alkali-resistant separation layer will not excessively affect the water flux of the membrane, thereby maintaining a good water flux.

[0100] In the present invention, if the concentration of the halogenated quaternary ammonium salt and / or the halogenated quaternary phosphonium salt in the first solution in step S1 is lower than the above range, the halogenated quaternary ammonium salt and / or the halogenated quaternary phosphonium salt in the first solution cannot fully react with the polyamine in the second solution; if the concentration of the halogenated quaternary ammonium salt and / or the halogenated quaternary phosphonium salt in the first solution in step S1 is higher than the above range, the above-mentioned halogenated quaternary ammonium salt and / or the halogenated quaternary phosphonium salt consumes too much amino groups in the polyamine structure in the second solution, so that the separation layer formed by interfacial polymerization in step S3 is not dense enough.

[0101] Furthermore, the concentration of the halogenated quaternary ammonium salt and / or the halogenated quaternary phosphonium salt in the first solution is 1 wt%-10 wt%.

[0102] According to the present invention, the catalyst is selected from at least one of sodium hydroxide, potassium hydroxide, potassium carbonate, sodium carbonate, sodium bicarbonate, potassium bicarbonate, disodium hydrogen phosphate and dipotassium hydrogen phosphate, preferably potassium hydroxide.

[0103] According to the present invention, the concentration of the catalyst in the first solution is 0.01 wt%-5 wt%.

[0104] In the present invention, when the concentration of the catalyst in the first solution in step S1 is controlled to meet the above range, it can ensure that the halogenated quaternary ammonium salt and / or halogenated quaternary phosphonium salt in the first solution can fully react with the polyamine in the second solution and have a high reaction rate, and the quaternary ammonium salt and / or quaternary phosphonium salt structure is introduced into the molecular structure of the polyamine in a relatively short time.

[0105] Furthermore, the concentration of the catalyst in the first solution is 0.1 wt%-1 wt%.

[0106] According to the present invention, in step S1, the polyamine is selected from at least one of polyethyleneimine, triethylenetetramine, tetraethylenepentamine, diethylenetriamine, polyethylenepolyamine, piperazine, m-phenylenediamine and p-phenylenediamine; preferably polyethyleneimine and / or polyethylenepolyamine.

[0107] According to the present invention, the concentration of the polyamine in the second solution is 1 wt%-20 wt%, preferably 5 wt%-10 wt%.

[0108] According to the present invention, the amounts of the first solution and the second solution are such that the mass ratio of the polyamine, the halogenated quaternary ammonium salt and / or the halogenated quaternary phosphonium salt, and the catalyst is 1-1000:1-100:1.

[0109] In the present invention, when the mass ratio of the polyamine, the halogenated quaternary ammonium salt and / or the halogenated quaternary phosphonium salt and the catalyst is controlled to meet the above range, it can be ensured that the halogenated quaternary ammonium salt and / or the halogenated quaternary phosphonium salt in the first solution can fully react with the polyamine in the second solution, and the reaction rate and reaction efficiency are both high, and more quaternary phosphonium salt and / or quaternary ammonium salt structures can be introduced into the polyamine in a relatively short time.

[0110] Furthermore, the amounts of the first solution and the second solution are such that the mass ratio of the polyamine, the halogenated quaternary ammonium salt and / or the halogenated quaternary phosphonium salt, and the catalyst is 1-200:1-50:1.

[0111] According to the present invention, in step S1, the reaction conditions include: reaction temperature of 25-90° C.; reaction time of 1-48 h.

[0112] In the present invention, when the conditions for controlling the reaction in step S1 satisfy the above range, it can ensure that the halogenated quaternary ammonium salt and / or halogenated quaternary phosphonium salt in the first solution can fully react with the polyamine in the second solution, and the reaction rate and reaction efficiency are both high, and more quaternary phosphonium salt and / or quaternary ammonium salt structures can be introduced into the polyamine in a shorter time.

[0113] Furthermore, in step S1, the reaction conditions include: reaction temperature of 40-60°C; reaction time of 6-24h.

[0114] In a preferred embodiment of the present invention, the first solution is added dropwise to the second solution containing the polyamine. By adding the first solution dropwise to the second solution containing the polyamine, the reaction rate can be controlled, and the first solution and the second solution are fully mixed to ensure that the quaternary ammonium halogenide and / or the quaternary phosphonium halogenide reacts fully with the polyamine.

[0115] According to the present invention, the dropping speed is 0.5-5 mL / min, preferably 1-3 mL / min.

[0116] In the present invention, there is no particular limitation on the method for preparing the porous supporting layer in the bottom layer in step S2, and it can be prepared by conventional methods in the art, preferably by a phase inversion method. Specifically, a polymer solution of the porous supporting layer material is coated on one surface of the bottom layer, and the porous supporting layer is obtained by phase inversion.

[0117] In the present invention, the phase inversion method can preferably be: dissolving the supporting layer polymer material in a solvent to obtain a polymer solution with a concentration of 10-20wt%, and degassing at 20-40°C for 10-180min; then coating the polymer solution on the bottom layer to obtain an initial membrane, and then soaking it in water at a temperature of 10-30°C for 10-60min to obtain the supporting layer polymer porous membrane through the phase inversion layer.

[0118] The solvent may be at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide.

[0119] In the present invention, the acid-base resistant separation layer is produced by interfacial polymerization of polyamines modified by quaternary ammonium halides and / or quaternary phosphonium halides and polypolar monomers.

[0120] According to the present invention, the polyvalent polar monomer is selected from at least one of polyvalent isocyanates, triazine compounds containing at least two C-Cl bonds, and polyvalent sulfonyl chlorides.

[0121] According to the present invention, the polyisocyanate is selected from at least one of meta-phenylenediisocyanate, isophorone diisocyanate, 1,6-hexamethylene diisocyanate, toluene-2,6-diisocyanate, 1,4-phenylenediisocyanate, toluene-2,4-diisocyanate, 4,4'-methylenebis(phenyl isocyanate), 1,3-phenylenediisocyanate, 3,3'-dichloro-4,4'-diisocyanatebiphenyl, dicyclohexylmethane-4,4'-diisocyanate, trimethylhexamethylene diisocyanate, L-lysine-ethyl ester-diisocyanate, 1,4-cyclohexyl diisocyanate and 4-chloro-6-methyl-meta-phenylenediisocyanate; preferably 1,4-phenylenediisocyanate and / or 1,3-phenylenediisocyanate.

[0122] According to the present invention, the triazine compound containing at least two C-Cl bonds is selected from at least one of cyanuric chloride, 2,4-dichloro-1,3,5-triazine, 2,5-dichloro-1,3,5-triazine and 2,4-dichloro-6-phenyl-1,3,5-triazine; preferably cyanuric chloride.

[0123] According to the present invention, the polysulfonyl chloride is selected from at least one of 1,3-benzenedisulfonyl chloride, 1,2-benzenedisulfonyl chloride, 1,4-benzenedisulfonyl chloride, 2,4-disulfonyl chloride-mesitylene, biphenyl-4,4'-disulfonyl chloride, 4,5-dichloro-1,3-benzenedisulfonyl chloride, 2,6-naphthalene disulfonyl chloride, 1,3-naphthalene disulfonyl chloride, 2,7-naphthalene disulfonyl chloride, 1,3,5-benzene trisulfonyl chloride and 1,3,6-naphthalene trisulfonyl chloride; preferably 1,3-benzenedisulfonyl chloride.

[0124] According to the present invention, the concentration of the modified polyamine in the aqueous phase is 0.1 wt%-10 wt%, preferably 0.5 wt%-2.5 wt%.

[0125] According to the present invention, the concentration of the multi-polar monomer in the organic phase is 0.01 wt%-2 wt%, preferably 0.05-1 wt%.

[0126] In the present invention, there is no particular limitation on the type of the solvent of the organic phase, as long as it can dissolve the polyacyl chloride. Preferably, the solvent of the organic phase is one or more of n-hexane, dodecane, n-heptane, and alkane solvent oil (Isopar E, Isopar G, Isopar H, Isopar L, and Isopar M).

[0127] In the present invention, in step S3, there is no special limitation on the conditions for interfacial polymerization between the modified polyamine and the polypolar monomer, and it can be carried out according to conventional conditions in the art. However, in order to enable the three layers to play a better synergistic role, the obtained positively charged acid- and alkali-resistant composite nanofiltration membrane can better have an excellent magnesium-lithium separation coefficient and a higher water flux. Preferably, the first contact time is 5-100s, preferably 10-60s; the second contact time is 10-200s, preferably 20-120s; the heat treatment conditions include: the heat treatment temperature is 40-150°C, preferably 50-120°C; the heat treatment time is 0.5-10min, preferably 1-5min.

[0128] The third aspect of the present invention provides a positively charged acid- and alkali-resistant composite nanofiltration membrane prepared by the above-mentioned preparation method.

[0129] A fourth aspect of the present invention provides an application of the above-mentioned positively charged acid- and alkali-resistant composite nanofiltration membrane in the field of water treatment and separation.

[0130] In the present invention, the MgCl 2 The desalination rate is ≥88%, preferably ≥90%; the LiCl desalination rate is ≥26%, preferably ≥28%; the magnesium-lithium separation coefficient is 10-90, preferably 25-86; the water flux is ≥22LMH, preferably ≥25LMH.

[0131] Other features and advantages of the present invention will be described in detail in the following detailed description.

[0132] The present invention will be described in detail below through examples.

[0133] (1) The water flux of the nanofiltration membrane is tested by the following method: the nanofiltration membrane is placed in a membrane pool, pre-pressed at 1.5 MPa for 1 h, and the water permeation of the positively charged acid-base resistant composite nanofiltration membrane is measured under the conditions of a pressure of 2 MPa and a temperature of 25°C within a certain period of time. The water flux is calculated by the following formula:

[0134] J = Q / (A·t), where J is the water flux, Q is the water permeation (L), and A is the effective filtration membrane area of ​​the positively charged acid- and alkali-resistant composite nanofiltration membrane (m 2 ), t is time (h).

[0135] (2) The salt rejection rate of the nanofiltration membrane was obtained by the following test method: a positively charged acid-base resistant composite nanofiltration membrane was placed in a membrane pool, pre-pressed at 1.5 MPa for 1 h, and the salt concentration changes in the raw aqueous solution and the permeate with an initial concentration of 2000 ppm within 1 h were tested at a pressure of 2 MPa and a temperature of 25°C. The salt rejection rate was calculated by the following formula:

[0136] R=(C f -C p ) / C f ×100%, where R is the desalination rate, C f is the concentration of magnesium chloride or lithium chloride in the original solution (measured by conductivity meter), C p is the concentration of magnesium chloride or lithium chloride in the permeate.

[0137] (3) The magnesium-lithium separation coefficient of the nanofiltration membrane was tested by the following method: a positively charged acid-base resistant composite nanofiltration membrane was placed in a membrane pool, the original aqueous solution was a mixture of 2000 ppm magnesium chloride and 100 ppm lithium chloride, and pre-pressed at 1.5 MPa for 1 h. Then, the permeate was obtained under the conditions of a pressure of 2 MPa and a temperature of 25°C. The mass concentrations of magnesium ions and lithium ions in the original solution and the permeate were measured by ion chromatography, and the lithium-magnesium separation coefficient was calculated by the following formula:

[0138]

[0139] Where S is the lithium-magnesium separation coefficient, C Mg,f and C Li,f are the mass concentrations of magnesium ions and lithium ions in the raw water (measured by ion chromatography); C Mg,p and C Li,p are the mass concentrations of magnesium ions and lithium ions in the permeate, respectively (measured by ion chromatography).

[0140] (4) Acid resistance test method of positively charged acid-resistant and alkali-resistant composite nanofiltration membrane: The nanofiltration membrane was immersed in a 5 wt% HCl solution for 7 days, taken out and thoroughly cleaned, and then the changes in the water flux and magnesium-lithium separation coefficient of the nanofiltration membrane were tested.

[0141] (5) Contact angle measurement of positively charged acid-base resistant composite nanofiltration membrane surface

[0142] The surface contact angle of the composite film sample was tested by the sessile drop method using a DSA100 surface contact angle meter produced by KRUSS, Germany. Before the test, the sample was dried in a vacuum oven at 60°C for 30 minutes to remove surface and internal moisture, and then the dried film was attached to a flat glass slide with double-sided tape. The volume of each water droplet during the test was 2 μL. The water droplet was dropped on the film surface for 3 seconds and then tested immediately. The average value was taken after multiple measurements to determine the final contact angle.

[0143] (6) Determination of the content of nitrogen atoms in the quaternary ammonium salt group in the positively charged acid-base resistant composite nanofiltration membrane and the content of phosphorus atoms in the positively charged acid-base resistant composite nanofiltration membrane:

[0144] Before measurement, the sample was dried in an oven to constant weight, and the elemental composition of the composite film sample surface was determined using a Sigma Probe X-ray photoelectron spectrometer produced by Thermo VG, UK. For samples containing quaternary ammonium salt groups, the molar content of nitrogen atoms in the quaternary ammonium salt groups is equal to the corresponding molar content of halogens, and the content of nitrogen atoms in the quaternary ammonium salt groups can be determined by the measured halogen content;

[0145] The content of phosphorus atoms in the quaternary phosphate salt in the positively charged acid- and alkali-resistant composite nanofiltration membrane can be directly measured by XPS spectroscopy.

[0146] (7) Pore size test of positively charged acid-base resistant composite nanofiltration membrane: PEG solute transfer method is used for measurement. The detailed steps are as follows:

[0147] (i) Testing the retention rate of positively charged acid-base resistant composite nanofiltration membrane for PEG with different molecular sizes;

[0148] (ii) Linear fitting is performed between the PEG size and the retention rate in a logarithmic-probability coordinate system, and the PEG size corresponding to the 50% retention rate is the average pore size of the positively charged acid-base resistant composite nanofiltration membrane.

[0149] (8) Zeta potential test on the surface of positively charged acid- and alkali-resistant composite nanofiltration membrane: The test was performed using a Surpass electrokinetic analyzer (Anton Paar), the circulating fluid was a dilute aqueous solution of KCl, and the pH of the test fluid was 7.

[0150] In addition, in the following examples and comparative examples:

[0151] Branched polyethyleneimine (weight average molecular weight of 25000 g / mol), polyethylene polyamine, 1,4-phenylene diisocyanate, cyanuric chloride, 1,3-phenylene disulfonyl chloride, 2-chloroethyltrimethylammonium chloride, 3-bromopropyltriphenylphosphonium bromide, 4-bromomethylbenzyltriphenylphosphonium bromide, chloromethyltriphenylphosphonium chloride, 2-chloroethyltrimethylammonium chloride, 3-bromopropyltrimethylammonium bromide, iodomethyltrimethylammonium iodide, etc. were purchased from J&K Technology Co., Ltd. Other chemical reagents were purchased from Sinopharm Chemical Reagent Co., Ltd.

[0152] The supporting layer is prepared by a phase inversion method, and the specific steps are as follows:

[0153] A certain amount of polysulfone (number average molecular weight of 80000 g / mol) was dissolved in N,N-dimethylformamide to prepare a polysulfone solution with a concentration of 18 wt%, and degassed at 25°C for 120 min; then, the polysulfone solution was coated on a polyester non-woven fabric (75 μm thick) using a scraper to obtain an initial membrane, which was then immersed in water at 25°C for 60 min to allow the polysulfone layer on the surface of the polyester non-woven fabric to undergo phase transformation into a porous membrane, and finally washed with water three times to obtain a support layer with a total thickness of 115 μm.

[0154] Example 1

[0155] (1) 5 g of polyethyleneimine was dissolved in 100 g of deionized water and heated to 60° C. under stirring; 10 g of 5 wt% 3-bromopropyltriphenylphosphonium bromide (X 1 With X as Br, R 5 ' is propylene, R 6 '、R 7 '、R 8 ' is phenyl) and 1wt% potassium hydroxide aqueous solution, after the addition is completed, maintain 60°C and continue the reaction for 24h; the mass ratio of polyamine, halogenated quaternary phosphonium salt and catalyst is 5:0.5:0.1=50:5:1.

[0156] (2) The quaternary phosphonium salt-modified polyethyleneimine aqueous solution prepared above was diluted with water to adjust the concentration of the quaternary phosphonium salt-modified polyethyleneimine aqueous solution to 0.5 wt %. 2 The upper surface of the polysulfone support layer is contacted with 50 mL of an aqueous solution containing 0.5 wt% of the quaternary phosphonium salt-modified polyethyleneimine prepared above, and the liquid is discharged after contacting at 25° C. for 60 s; then, the upper surface of the support layer is contacted with 30 mL of an Isopar E solution containing 0.1 wt% of 1,4-phenylene diisocyanate, and the liquid is discharged after contacting at 25° C. for 60 s; then, the membrane is placed in an oven and heated at 70° C. for 3 min to obtain a positively charged acid-base resistant composite nanofiltration membrane N1;

[0157] The infrared spectrum of positively charged acid-base resistant composite nanofiltration membrane N1 is as follows Figure 1 As shown. Figure 1 It can be seen that the -1 The characteristic peak of the CP bond at , which indicates that the quaternary phosphorus group in the structure of 3-bromopropyltriphenylphosphonium bromide is successfully modified on the surface of the nanofiltration membrane, thereby enhancing the positive charge of the surface of the positively charged acid- and alkali-resistant composite nanofiltration membrane and improving the magnesium-lithium separation performance of the membrane.

[0158] Example 2

[0159] The preparation method is the same as that of Example 1, except that "polyethylene polyamine" is used to replace "polyethylene imine" to obtain a positively charged acid- and alkali-resistant composite nanofiltration membrane N2.

[0160] Example 3

[0161] The preparation method is the same as that of Example 1, except that "4-bromomethylbenzyltriphenylphosphonium bromide (X 1 and X is Br, R 5 ' is a C1 arylmethyl group, R 6 '、R 7 '、R 8 ' is phenyl)" replaces "3-bromopropyltriphenylphosphonium bromide" to obtain a positively charged acid- and alkali-resistant composite nanofiltration membrane N3.

[0162] Example 4

[0163] The preparation method is the same as that of Example 1, except that "chloromethyl triphenylphosphonium chloride (R 5 ' is methylene, R 6 '、R 7 '、R 8 ' is phenyl, X 1 and X is Cl)" to replace "3-bromopropyltriphenylphosphonium bromide" to obtain the positively charged acid and alkali resistant composite nanofiltration membrane N4.

[0164] Example 5

[0165] (1) 5 g of polyethyleneimine was dissolved in 100 g of deionized water and heated to 60° C. under stirring; 10 g of 5 wt % 2-chloroethyltrimethylammonium chloride (X and X) was added dropwise to the solution at a rate of 2 mL / min. 1 Cl, R 1 ' is ethylene, R 2 '、R 3 '、R 4 ' is methyl) and 1wt% potassium hydroxide aqueous solution, after the addition is completed, maintain 60°C and continue the reaction for 24h; the mass ratio of polyamine, halogenated quaternary ammonium salt and catalyst is 5:0.5:0.1=50:5:1.

[0166] (2) The quaternary ammonium salt-modified polyethyleneimine aqueous solution prepared above was diluted with water to adjust the concentration of the quaternary ammonium salt-modified polyethyleneimine aqueous solution to 0.5 wt %. 2The upper surface of the polysulfone support layer is contacted with 50 mL of an aqueous solution containing 0.5 wt % of the quaternary ammonium salt modified polyethyleneimine prepared above, and the liquid is discharged after contacting at 25° C. for 60 s; then, the upper surface of the support layer is contacted with 30 mL of an Isopar E solution containing 0.1 wt % of 1,4-phenylene diisocyanate, and the liquid is discharged after contacting at 25° C. for 60 s; then, the membrane is placed in an oven and heated at 70° C. for 3 min to obtain a positively charged acid- and alkali-resistant composite nanofiltration membrane N5.

[0167] Example 6

[0168] The preparation method is the same as that of Example 5, except that "3-bromopropyltrimethylammonium bromide (X and X 1 Br, R 1 ' is propylene, R 2 '、R 3 '、R 4 ' is methyl)" replaces "2-chloroethyltrimethylammonium chloride" to obtain a positively charged acid- and alkali-resistant composite nanofiltration membrane N6.

[0169] Example 7

[0170] The preparation method is the same as that of Example 5, except that "iodomethyltrimethylammonium iodide (X and X 1 I, R 1 ' is methylene, R 2 '、R 3 '、R 4 ' is methyl)" replaces "2-chloroethyltrimethylammonium chloride" to obtain the positively charged acid and alkali resistant composite nanofiltration membrane N7.

[0171] Example 8

[0172] (1) Dissolve 5 g of polyethyleneimine in 100 g of deionized water and heat to 60° C. under stirring; add 10 g of an aqueous solution containing 5 wt % of 3-bromopropyltriphenylphosphonium bromide and 1 wt % of potassium hydroxide to the solution at a rate of 2 mL / min. After the addition is complete, keep the temperature at 60° C. and continue the reaction for 24 h;

[0173] (2) The quaternary phosphonium salt-modified polyethyleneimine aqueous solution prepared above was diluted with water to adjust the concentration of the quaternary phosphonium salt-modified polyethyleneimine aqueous solution to 2 wt %. 2The upper surface of the polysulfone support layer is contacted with 50 mL of an aqueous solution containing 2 wt % of the quaternary phosphonium salt modified polyethyleneimine prepared above, and the liquid is discharged after contacting at 25° C. for 60 s; then, the upper surface of the support layer is contacted with 30 mL of an Isopar E solution containing 0.05 wt % of cyanuric chloride, and the liquid is discharged after contacting at 25° C. for 60 s; then, the membrane is placed in an oven and heated at 70° C. for 3 min to obtain a positively charged acid- and alkali-resistant composite nanofiltration membrane N8.

[0174] Example 9

[0175] (1) Dissolve 5 g of polyethyleneimine in 100 g of deionized water and heat to 60° C. under stirring; add 10 g of an aqueous solution containing 5 wt % of 3-bromopropyltriphenylphosphonium bromide and 1 wt % of potassium hydroxide to the solution at a rate of 2 mL / min. After the addition is complete, keep the temperature at 60° C. and continue the reaction for 24 h;

[0176] (2) The quaternary phosphonium salt-modified polyethyleneimine aqueous solution prepared above was diluted with water to adjust the concentration of the quaternary phosphonium salt-modified polyethyleneimine aqueous solution to 2 wt %. 2 The upper surface of the polysulfone support layer is contacted with 50 mL of an aqueous solution containing 2 wt% of the quaternary phosphonium salt modified polyethyleneimine prepared above, and the liquid is discharged after contacting at 25°C for 60 seconds; then, the upper surface of the support layer is contacted with 30 mL of an Isopar E solution containing 0.2 wt% of 1,3-benzenedisulfonyl chloride, and the liquid is discharged after contacting at 25°C for 60 seconds; then, the membrane is placed in an oven and heated at 70°C for 3 minutes to obtain a positively charged acid- and alkali-resistant composite nanofiltration membrane N9.

[0177] Example 10

[0178] The preparation method is the same as that in Example 1, except that "adding 10 g of 0.5 wt% 3-bromopropyltriphenyl phosphonium bromide to the solution at a rate of 2 mL / min" is used instead of "adding 10 g of 5 wt% 3-bromopropyltriphenyl phosphonium bromide to the solution at a rate of 2 mL / min" to obtain the positively charged acid and alkali resistant composite nanofiltration membrane N10.

[0179] Embodiment 11

[0180] The preparation method is the same as that in Example 1, except that "adding 10 g of 8 wt% 3-bromopropyltriphenyl phosphonium bromide to the solution at a rate of 2 mL / min" is used instead of "adding 10 g of 5 wt% 3-bromopropyltriphenyl phosphonium bromide to the solution at a rate of 2 mL / min" to obtain the positively charged acid and alkali resistant composite nanofiltration membrane N11.

[0181] Example 12

[0182] The preparation method is the same as that in Example 1, except that "adding 10 g of 0.2 wt% 3-bromopropyltriphenyl phosphonium bromide to the solution at a rate of 2 mL / min" is used instead of "adding 10 g of 5 wt% 3-bromopropyltriphenyl phosphonium bromide to the solution at a rate of 2 mL / min" to obtain the positively charged acid and alkali resistant composite nanofiltration membrane N12.

[0183] Embodiment 13

[0184] The preparation method is the same as that in Example 1, except that "10 g of an aqueous solution containing 5 wt% of 3-bromopropyltriphenylphosphonium bromide and 0.05 wt% of potassium hydroxide is added dropwise to the solution at a rate of 2 mL / min" instead of "10 g of an aqueous solution containing 5 wt% of 3-bromopropyltriphenylphosphonium bromide and 1 wt% of potassium hydroxide is added dropwise to the solution at a rate of 2 mL / min" to obtain a positively charged acid- and alkali-resistant composite nanofiltration membrane N13; the mass ratio of the polyamine, the halogenated quaternary phosphonium salt and the catalyst is 5:0.5:0.005=1000:100:1.

[0185] Embodiment 14

[0186] The preparation method is the same as that in Example 1, except that "10 g of an aqueous solution containing 5 wt% of 3-bromopropyltriphenylphosphonium bromide and 0.5 wt% of potassium hydroxide is added dropwise to the solution at a rate of 2 mL / min" instead of "10 g of an aqueous solution containing 5 wt% of 3-bromopropyltriphenylphosphonium bromide and 1 wt% of potassium hydroxide is added dropwise to the solution at a rate of 2 mL / min" to obtain a positively charged acid- and alkali-resistant composite nanofiltration membrane N14; the mass ratio of the polyamine, the halogenated quaternary phosphonium salt and the catalyst is 5:0.5:0.05=100:10:1.

[0187] Embodiment 15

[0188] The preparation method is the same as that in Example 1, except that "10 g of an aqueous solution containing 5 wt% of 3-bromopropyltriphenylphosphonium bromide and 0.005 wt% of potassium hydroxide is added dropwise to the solution at a rate of 2 mL / min" instead of "10 g of an aqueous solution containing 5 wt% of 3-bromopropyltriphenylphosphonium bromide and 1 wt% of potassium hydroxide is added dropwise to the solution at a rate of 2 mL / min" to obtain a positively charged acid- and alkali-resistant composite nanofiltration membrane N15; the mass ratio of the polyamine, the halogenated quaternary phosphonium salt and the catalyst is 5:0.5:0.0005=10000:1000:1.

[0189] Example 16

[0190] The preparation method is the same as that in Example 1, except that "10 g of 5 wt% 3-bromopropyltriphenyl phosphonium bromide is added dropwise to the solution at a rate of 2 mL / min" instead of "10 g of 5 wt% 3-bromopropyltriphenyl phosphonium bromide is added dropwise to the solution at a rate of 2 mL / min" to obtain the positively charged acid- and alkali-resistant composite nanofiltration membrane N16; the mass ratio of the polyamine, the halogenated quaternary ammonium salt and the halogenated quaternary phosphonium salt to the catalyst is 5:0.5:0.1=50:5:1.

[0191] Embodiment 17

[0192] (1) Dissolve 5 g of polyethyleneimine in 100 g of deionized water and place the above-mentioned 400 cm 2 The upper surface of the polysulfone support layer is contacted with 50 mL of an aqueous solution containing 0.5 wt% polyethyleneimine, and the liquid is discharged after contacting at 25° C. for 60 seconds; then, the upper surface of the support layer is contacted with 30 mL of an Isopar E solution containing 0.1 wt% 1,4-phenylene diisocyanate, and the liquid is discharged after contacting at 25° C. for 60 seconds; then, the membrane is placed in an oven and heated at 70° C. for 3 minutes to obtain a composite membrane;

[0193] (2) The obtained composite nanofiltration membrane was immersed in 150 g of an aqueous solution containing 10 wt % of 3-bromopropyltriphenylphosphonium bromide and 0.5 wt % of potassium hydroxide for 1 min, then taken out and dried at 70° C. for 5 min to obtain a quaternary phosphonium salt-modified nanofiltration membrane N17.

[0194] Embodiment 18

[0195] (1) Dissolve 5 g of polyethyleneimine in 100 g of deionized water and place the above-mentioned 400 cm 2 The upper surface of the polysulfone support layer is contacted with 50 mL of an aqueous solution containing 2 wt% polyethyleneimine, and the liquid is discharged after the contact is carried out at 25° C. for 60 seconds; then, the upper surface of the support layer is contacted with 30 mL of an Isopar E solution containing 0.05 wt% cyanuric chloride, and the liquid is discharged after the contact is carried out at 25° C. for 60 seconds; then, the membrane is placed in an oven and heated at 70° C. for 3 minutes to obtain a composite membrane;

[0196] (2) The obtained composite nanofiltration membrane was immersed in 150 g of an aqueous solution containing 10 wt % of 3-bromopropyltriphenylphosphonium bromide and 0.5 wt % of potassium hydroxide for 1 min, then taken out and dried at 70° C. for 5 min to obtain a quaternary phosphonium salt-modified nanofiltration membrane N18.

[0197] Embodiment 19

[0198] (1) Dissolve 5 g of polyethyleneimine in 100 g of deionized water and place the above-mentioned 400 cm 2The upper surface of the polysulfone support layer is contacted with 50 mL of an aqueous solution containing 2 wt% polyethyleneimine, and the liquid is discharged after the contact is carried out at 25° C. for 60 seconds; then, the upper surface of the support layer is contacted with 30 mL of an Isopar E solution containing 0.2 wt% 1,3-benzenedisulfonyl chloride, and the liquid is discharged after the contact is carried out at 25° C. for 60 seconds; then, the membrane is placed in an oven and heated at 70° C. for 3 minutes to obtain a composite membrane;

[0199] (2) The obtained composite nanofiltration membrane was immersed in 150 g of an aqueous solution containing 10 wt % of 3-bromopropyltriphenylphosphonium bromide and 0.5 wt % of potassium hydroxide for 1 min, then taken out and dried at 70° C. for 5 min to obtain a quaternary phosphonium salt-modified nanofiltration membrane N19.

[0200] Comparative Example 1

[0201] Dissolve 5 g of polyethyleneimine in 100 g of deionized water and place the above-mentioned 2 The upper surface of the polysulfone support layer was contacted with 50 mL of an aqueous solution containing 0.5 wt% polyethyleneimine, and the liquid was discharged after contacting at 25°C for 60 seconds; then, the upper surface of the support layer was contacted with 30 mL of an Isopar E solution containing 0.1 wt% 1,4-phenylene diisocyanate, and the liquid was discharged after contacting at 25°C for 60 seconds; then, the membrane was placed in an oven and heated at 70°C for 3 minutes to obtain a nanofiltration membrane D1.

[0202] Comparative Example 2

[0203] Dissolve 5 g of polyethyleneimine in 100 g of deionized water and place the above-mentioned 2 The upper surface of the polysulfone support layer was contacted with 50 mL of an aqueous solution containing 2 wt% polyethyleneimine at 25°C for 60 seconds, and then the liquid was drained; then, the upper surface of the support layer was contacted with 30 mL of an Isopar E solution containing 0.05 wt% cyanuric chloride at 25°C for 60 seconds, and then the liquid was drained; then, the membrane was placed in an oven and heated at 70°C for 3 minutes to obtain a nanofiltration membrane D2.

[0204] Comparative Example 3

[0205] Dissolve 5 g of polyethyleneimine in 100 g of deionized water and place the above-mentioned 2 The upper surface of the polysulfone support layer was contacted with 50 mL of an aqueous solution containing 2 wt% polyethyleneimine at 25°C for 60 seconds, and then the liquid was drained; then, the upper surface of the support layer was contacted with 30 mL of an Isopar E solution containing 0.2 wt% 1,3-benzenedisulfonyl chloride at 25°C for 60 seconds, and then the liquid was drained; then, the membrane was placed in an oven and heated at 70°C for 3 minutes to obtain a nanofiltration membrane D3.

[0206] The thickness of the positively charged acid- and alkali-resistant composite nanofiltration membrane prepared in the example and the nanofiltration membrane prepared in the comparative example were tested, and the results are shown in Table 1.

[0207] The surface Zeta potential, average pore size, the content of nitrogen atoms in the quaternary ammonium salt groups in the positively charged acid- and alkali-resistant composite nanofiltration membrane, the content of phosphorus atoms in the positively charged acid- and alkali-resistant composite nanofiltration membrane and the contact angle of the positively charged acid- and alkali-resistant composite nanofiltration membrane obtained in the embodiment and the nanofiltration membrane obtained in the comparative example were tested, and the results are shown in Table 2.

[0208] The water flux, the salt rejection rate of magnesium chloride and lithium chloride, and the magnesium-lithium separation coefficient of the positively charged acid-resistant composite nanofiltration membrane obtained in the embodiment and the nanofiltration membrane obtained in the comparative example were compared; the magnesium-lithium separation coefficient and the water flux of the positively charged acid-resistant composite nanofiltration membrane obtained in the embodiment and the nanofiltration membrane obtained in the comparative example were tested after acid treatment, and the results are shown in Table 3.

[0209] Table 1

[0210]

[0211] Note: The thickness of the acid-base resistant separation layer here refers to the acid-base resistant separation layer grafted with quaternary ammonium salt groups / quaternary phosphonium salt groups.

[0212] Table 2

[0213]

[0214] Note: a - The content of nitrogen atoms in the quaternary ammonium salt group;

[0215] b -The content of phosphorus atoms in the positively charged acid- and alkali-resistant composite nanofiltration membrane;

[0216] “-” means it cannot be measured.

[0217] Table 3

[0218]

[0219]

[0220] It can be seen from Tables 1-3 that the positively charged acid- and alkali-resistant composite nanofiltration membrane of the present invention can better combine excellent magnesium-lithium separation coefficient and higher water flux.

[0221] It can be seen from Table 2 that, compared with the comparative example, in the positively charged acid- and alkali-resistant composite nanofiltration membrane prepared in the embodiment, due to the biochemical reaction of the halogenated quaternary ammonium salt and / or quaternary phosphonium salt with the polyamine under the action of an alkaline catalyst, the positively charged quaternary ammonium salt groups and / or quaternary phosphonium salt groups are modified into the polyamine molecules, and after interfacial polymerization, the membrane surface potential of the obtained positively charged acid- and alkali-resistant composite nanofiltration membrane is significantly improved.

[0222] On the other hand, due to the introduction of quaternary ammonium salt groups or quaternary phosphonium salt groups, the interfacial polymerization is regulated and the polymerization reaction proceeds more fully, so that the separation layer of the positively charged acid- and alkali-resistant composite nanofiltration membrane finally prepared is denser and has a smaller pore size. The positively charged acid- and alkali-resistant composite nanofiltration membrane has a higher magnesium-lithium separation coefficient while maintaining a high water flux.

[0223] It can be seen from the results in Table 3 that, compared with Example 17, Example 18 and Example 19, in Examples 1-16, the polyamine is first subjected to positive charge modification and then interfacial polymerization is performed. After interfacial polymerization, the retention rate of magnesium chloride obtained by the membrane is significantly improved, and the magnesium-lithium separation coefficient is significantly increased. This is mainly attributed to the enhancement of the positive charge of the membrane surface and the improvement of the density of the separation layer (the density is characterized by the average pore size).

[0224] On the other hand, it can be seen from the "magnesium-lithium separation coefficient after 7 days of treatment with 5wt% HCl" that the magnesium-lithium separation coefficient and water flux of the membrane remain basically unchanged after strong acid treatment, indicating that the positively charged acid-resistant and alkali-resistant composite nanofiltration membrane prepared by positively charged modified polyamine has better acid / alkali resistance.

[0225] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A positively charged acid- and alkali-resistant composite nanofiltration membrane, characterized in that: The positively charged acid- and alkali-resistant composite nanofiltration membrane comprises a bottom layer, a porous middle layer and an acid- and alkali-resistant separation layer in sequence; Wherein, the acid-base resistant separation layer is grafted with the quaternary ammonium salt group shown in formula I and / or the quaternary phosphonium salt group shown in formula II by N atom; Wherein, R1 is a substituted or unsubstituted alkylene group of C1-C9; R2, R3, and R4 are each independently selected from a C1-C3 alkyl group or a phenyl group; R5 is a C1-C6 alkylene group, a phenyl group, or a C7-C10 aralkyl group; R6, R7, and R8 are each independently selected from a phenyl group or a C7-C10 aralkyl group; X is halogen.

2. The positively charged acid- and alkali-resistant composite nanofiltration membrane according to claim 1, wherein: R1 is a C1-C6 substituted or unsubstituted alkylene or phenyl group, R2, R3, and R4 are each independently CH3; R5 is a C1-C3 alkylene, phenyl, or C8-C10 aralkyl group; R6, R7, and R8 are each independently phenyl; Preferably, R1 is an unsubstituted C1-C3 alkylene group, wherein the substituent is a hydroxyl group or a carboxyl group, preferably a hydroxyl group; Preferably, X is Cl, Br or I; Preferably, the acid-base resistant separation layer is selected from at least one of a polyurea separation layer, a polytriazineamine separation layer, a polysulfonamide separation layer, a poly(triazineamine-urea) separation layer, a poly(sulfonamide-urea) separation layer, a poly(triazineamine-sulfonamide) separation layer and a poly(triazineamine-sulfonamide-urea) separation layer, preferably at least one of a polyurea separation layer, a polytriazineamine separation layer and a polysulfonamide separation layer.

3. The positively charged acid- and alkali-resistant composite nanofiltration membrane according to claim 1 or 2, wherein: The content of nitrogen atoms in the quaternary ammonium salt groups in the positively charged acid-base resistant composite nanofiltration membrane is 10-20 at.%, preferably 10-15 at.%; Preferably, the content of phosphorus atoms in the positively charged acid- and alkali-resistant composite nanofiltration membrane is 0.4-3 at.%, preferably 0.5-2 at.%.

4. The positively charged acid- and alkali-resistant composite nanofiltration membrane according to any one of claims 1 to 3, wherein: The surface Zeta potential of the positively charged acid- and alkali-resistant composite nanofiltration membrane is 0-30 mV, preferably 5-25 mV.

5. The positively charged acid- and alkali-resistant composite nanofiltration membrane according to any one of claims 1 to 4, wherein: The average pore size of the positively charged acid- and alkali-resistant composite nanofiltration membrane is 0.1-0.4 nm, preferably 0.2-0.3 nm.

6. The positively charged acid- and alkali-resistant composite nanofiltration membrane according to any one of claims 1 to 5, wherein: The contact angle of the positively charged acid- and alkali-resistant composite nanofiltration membrane is 30-80°, preferably 30-60°.

7. The positively charged acid- and alkali-resistant composite nanofiltration membrane according to any one of claims 1 to 6, wherein: The thickness of the bottom layer is 30-150 μm, preferably 50-120 μm; Preferably, the thickness of the porous support layer is 10-100 μm, preferably 30-60 μm; Preferably, the thickness of the acid-base resistant separation layer is 10-500 nm, preferably 50-300 nm.

8. A method for preparing a positively charged acid- and alkali-resistant composite nanofiltration membrane, characterized in that: The preparation method comprises the following steps: S1. Under stirring conditions, adding a first solution containing a quaternary ammonium halogenate salt and / or a quaternary phosphonium halogenate salt and a catalyst to a second solution containing a polyamine to react and obtain a modified polyamine; S2, preparing a porous supporting layer on the bottom layer; S3, after the surface of the porous support layer is first contacted with the aqueous phase containing the modified polyamine in step S1, and then secondly contacted with the organic phase containing the polyvalent polar monomer, heat-treated to obtain the positively charged acid-base resistant composite nanofiltration membrane; The halogenated quaternary ammonium salt has a structure shown in formula III; the halogenated quaternary phosphonium salt has a structure shown in formula IV; wherein R1' is a C1-C9 substituted or unsubstituted alkylene group; R2', R3', and R4' are each independently selected from a C1-C3 alkyl group or a phenyl group; R5' is a C1-C6 alkylene group, a phenyl group, or a C7-C10 aralkyl group; R6', R 7’ , R8' are each independently phenyl or C7-C10 aralkyl; X and X1 are each independently halogen.

9. The preparation method according to claim 8, wherein: R1' is a C1-C6 substituted or unsubstituted alkylene group; R2', R3', and R4' are each independently CH3; R5' is a phenyl group or a C8-C10 aralkyl group; R6', R7', and R8' are each independently phenyl group; Preferably, R1' is an unsubstituted C1-C3 alkylene group, wherein the substituent is a hydroxyl group or a carboxyl group, preferably a hydroxyl group; Preferably, X is Cl, Br or I; Preferably, X1 is F, Cl, Br or I.

10. The preparation method according to claim 8 or 9, wherein: In step S1, the halogenated quaternary ammonium salt is selected from at least one of 2-chloroethyltrimethylammonium chloride, 2-chloroethyltriethylammonium chloride, 2-chloroethyltriphenylammonium chloride, 3-chloro-2-hydroxypropyltrimethylammonium chloride, 3-chloropropyltrimethylammonium chloride, 4-chlorobutyltrimethylammonium chloride, 5-chloropentyltrimethylammonium chloride, 6-chlorohexyltrimethylammonium chloride, 2-bromoethyltrimethylammonium bromide, 3-bromopropyltrimethylammonium bromide, 4-bromobutyltrimethylammonium bromide, 5-bromopentyltrimethylammonium bromide, 6-bromohexyltrimethylammonium bromide, iodomethyltrimethylammonium iodide, 2-iodoethyltrimethylammonium iodide, 3-iodopropyltrimethylammonium iodide, 4-iodobutyltrimethylammonium iodide, 5-iodopentyltrimethylammonium iodide and 6-iodohexyltrimethylammonium iodide; preferably 2-chloroethyltrimethylammonium chloride and / or 3-bromopropyltrimethylammonium bromide; Preferably, the halogenated quaternary phosphonium salt is selected from 3-bromopropyltriphenylphosphonium bromide, 2-bromoethyltriphenylphosphonium bromide, 1-bromoethyltriphenylphosphonium bromide, bromomethyltriphenylphosphonium bromide, 3-chloropropyltriphenylphosphonium chloride, 2-chloroethyltriphenylphosphonium chloride, 1-chloroethyltriphenylphosphonium chloride, chloromethyltriphenylphosphonium chloride, 3-iodopropyltriphenylphosphonium iodide, 2-iodoethyltriphenylphosphonium iodide, 1-iodoethyltriphenylphosphonium iodide, iodomethyltriphenylphosphonium bromide, 4-bromomethylbenzylphosphonium At least one of 2-bromomethylbenzyltriphenylphosphonium bromide, 2-bromomethylbenzyltriphenylphosphonium bromide, 3-bromomethylbenzyltriphenylphosphonium bromide, 4-chloromethylbenzyltriphenylphosphonium chloride, 2-chloromethylbenzyltriphenylphosphonium chloride, 3-chloromethylbenzyltriphenylphosphonium chloride, 4-iodomethylbenzyltriphenylphosphonium iodide, 2-iodomethylbenzyltriphenylphosphonium iodide and 3-iodomethylbenzyltriphenylphosphonium iodide; preferably 3-bromopropyltriphenylphosphonium bromide and / or 4-bromomethylbenzyltriphenylphosphonium bromide; Preferably, the catalyst is selected from at least one of sodium hydroxide, potassium hydroxide, potassium carbonate, sodium carbonate, sodium bicarbonate, potassium bicarbonate, disodium hydrogen phosphate and dipotassium hydrogen phosphate; preferably potassium hydroxide; Preferably, the concentration of the halogenated quaternary ammonium salt and / or the halogenated quaternary phosphonium salt in the first solution is 0.5wt%-20wt%, preferably 1wt%-10wt%; Preferably, the concentration of the catalyst in the first solution is 0.01 wt%-5 wt%, preferably 0.1 wt%-1 wt%.

11. The preparation method according to any one of claims 9 to 10, wherein: In step S1, the polyamine is selected from at least one of polyethyleneimine, polyethyleneamine, triethylenetetramine, tetraethylenepentamine, diethylenetriamine, polyethylenepolyamine, piperazine, m-phenylenediamine and p-phenylenediamine; preferably polyethyleneimine and / or polyethylenepolyamine; Preferably, the concentration of the polyamine in the second solution is 1wt%-20wt%, preferably 5wt%-10wt%; Preferably, the first solution and the second solution are used in such amounts that the mass ratio of the polyamine, the halogenated quaternary ammonium salt and / or the halogenated quaternary phosphonium salt, and the catalyst is 1-1000:1-100:1, preferably 1-200:1-50:

1.

12. The preparation method according to any one of claims 8 to 11, wherein: In step S1, the reaction conditions include: reaction temperature of 25-90°C, preferably 40-60°C; reaction time of 1-48h, preferably 6-24h.

13. The preparation method according to any one of claims 8 to 12, wherein: In step S3, the first contact time is 5-100 s, preferably 10-60 s; Preferably, the second contact time is 10-200s, preferably 20-120s; Preferably, the heat treatment conditions include: heat treatment temperature of 40-150° C., preferably 50-120° C.; heat treatment time of 0.5-10 min, preferably 1-5 min.

14. The preparation method according to any one of claims 8 to 13, wherein: In step S3, the polyvalent polar monomer is selected from at least one of polyvalent isocyanate, a triazine compound containing at least two C-Cl bonds, and polyvalent sulfonyl chloride; Preferably, the polyisocyanate is selected from at least one of meta-phenylenediisocyanate, isophorone diisocyanate, 1,6-hexamethylene diisocyanate, toluene-2,6-diisocyanate, 1,4-phenylenediisocyanate, toluene-2,4-diisocyanate, 4,4'-methylenebis(phenyl isocyanate), 1,3-phenylenediisocyanate, 3,3'-dichloro-4,4'-diisocyanate biphenyl, dicyclohexylmethane-4,4'-diisocyanate, trimethylhexamethylene diisocyanate, L-lysine-ethyl ester-diisocyanate, 1,4-cyclohexyl diisocyanate and 4-chloro-6-methyl meta-phenylenediisocyanate; preferably 1,4-phenylenediisocyanate and / or 1,3-phenylenediisocyanate; Preferably, the triazine compound containing at least two C-Cl bonds is selected from at least one of cyanuric chloride, 2,4-dichloro-1,3,5-triazine, 2,5-dichloro-1,3,5-triazine and 2,4-dichloro-6-phenyl-1,3,5-triazine; preferably cyanuric chloride; Preferably, the polysulfonyl chloride is selected from at least one of 1,3-benzenedisulfonyl chloride, 1,2-benzenedisulfonyl chloride, 1,4-benzenedisulfonyl chloride, 2,4-disulfonyl chloride-mesitylene, biphenyl-4,4'-disulfonyl chloride, 4,5-dichloro-1,3-benzenedisulfonyl chloride, 2,6-naphthalenedisulfonyl chloride, 1,3-naphthalenedisulfonyl chloride, 2,7-naphthalenedisulfonyl chloride, 1,3,5-benzenetrisulfonyl chloride and 1,3,6-naphthalenetrisulfonyl chloride; preferably 1,3-benzenedisulfonyl chloride; Preferably, the concentration of the modified polyamine in the aqueous phase is 0.1wt%-10wt%, preferably 0.5wt%-2.5wt%; Preferably, the concentration of the multi-polar monomer in the organic phase is 0.01 wt%-2 wt%, preferably 0.05-1 wt%.

15. A positively charged acid- and alkali-resistant composite nanofiltration membrane prepared by the preparation method described in any one of claims 8 to 14.

16. Use of the positively charged acid- and alkali-resistant composite nanofiltration membrane described in any one of claims 1 to 7 and 15 in the field of water treatment and separation.

Citation Information

Patent Citations

  • Phosphonic chloride monomer, nanofiltration composite membrane and preparation method of nanofiltration composite membrane

    CN107176963A

  • Nano-filtration membrane, preparation method and applications of thereof

    CN109692585A

  • Anti-biological contamination reverse osmosis membrane, and preparation method and application thereof

    CN110354682A

  • Acid / alkali-resistant composite nanofiltration membrane as well as preparation method and application thereof

    CN113509839A

  • High-performance thin-film composite nanofiltration membrane as well as preparation method and application thereof

    CN115337801A